2011
DOI: 10.1007/s12011-011-9113-y
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Gas Production and Dry Matter Degradability of Diets Consumed by Goats with or Without Copper and Zinc Supplementation

Abstract: An in vitro gas production technique was used to evaluate the effects of copper and zinc supplementation on the amount and rate of gas production, dry matter degradability (IVDMD), utilization of metabolizable energy (ME), and ruminal fermentation patterns using rumen fluid from four Boer male goats as inoculum. The goats were fed twice daily at 07:00 and 19:00 h a total mixed ration containing 10.3 and 22.5 mg/kg DM of Cu and Zn, respectively. This diet was incubated in vitro for 96 h with four treatments bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
2
19
0
1
Order By: Relevance
“…The increased IVDMD with Zn supplementation in the current study is consistent with the report of VazquezArmijo et al (13), who reported that adding 5.6 mg Zn/kg DM to a basal diet containing 22.5 mg/kg Zn increased IVDMD. In contrast, Arelovich et al (25) observed a negative effect of high levels of Zn supplementation on IVDMD.…”
Section: In Vivo Digestibility and Gas Production Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…The increased IVDMD with Zn supplementation in the current study is consistent with the report of VazquezArmijo et al (13), who reported that adding 5.6 mg Zn/kg DM to a basal diet containing 22.5 mg/kg Zn increased IVDMD. In contrast, Arelovich et al (25) observed a negative effect of high levels of Zn supplementation on IVDMD.…”
Section: In Vivo Digestibility and Gas Production Parameterssupporting
confidence: 93%
“…Similarly, Vazquez-Armijo et al (13) observed increased asymptotic gas production by adding 5.6 mg/ kg Zn to a basal diet containing 22.5 mg/kg Zn when compared to the control group (with no addition of Zn supplementation). Sobhanirad et al (24) reported that supplementation of rumen fluid with Zn supplements had no effect on gas production parameters during wheat straw fermentation.…”
Section: In Vivo Digestibility and Gas Production Parametersmentioning
confidence: 88%
See 1 more Smart Citation
“…8 Also, bacterial growth is greater with a Cu amount below 0.5 mg kg −1 DM in the growth medium; but when the concentration of the mineral exceeds this level, there is bacterial proteolysis. 9 Other studies report Cu requirements for ruminal bacteria in the range of 1-50 mg kg −1 DM. 1 Nevertheless, the Cu requirement to optimize bacterial metabolism and growth and the effect on methanogens in the rumen are not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Cu dosages of 10.3 mg kg −1 DM increased gas production. 9 However, extremely high doses of CuSO 4 from 0.2 to 0.4% in a ruminal in vitro culture reduce emissions of CH 4 . 12 This study was conducted www.soci.org D Hernández-Sánchez et al…”
Section: Introductionmentioning
confidence: 99%